Affective Filters’ Extent of Influence on Oral Communication: L2 Learners’ Perceptions - Henry E. Lemana II; Daryl B. Casamorin; Angelica D. Aguilar; Leny G. Paladin; Joycel V. Laureano; Jean A. Frediles (International Journal of Educational Management and Development Studies, 2023)
Second language (L2) learners are taught to speak English to be able to communicate effectively like when debating a topic and conversing about everyday topics. However, studies suggest that L2 students feel unmotivated, unconfident, and anxious speaking English in and out of classroom environments, which then creates an impact on the development of their language proficiency and efficiency. This paper primarily aimed to determine the affective filter’s extent of influence on oral communication based on the perception of senior high school ESL students in a southern Philippine private school. Using the descriptive-quantitative design, data were gathered via a survey questionnaire from a total of 258 senior high school students. Results reveal that students’ affective filters generally influence their oral communication to a moderate extent. Among Krashen’s identified affective filters (self-motivation, self-confidence, and anxiety), three indicators of self-motivation garnered the highest mean ratings and standard deviation scores. The results show that students’ oral communication is most influenced by their motivation to learn the target language, which in turn makes the learning process fun and gives them real-world opportunities to use the language. The study’s pedagogical implications for the future of language education include a call for teachers to maintain high levels of student motivation, assist their students in building self-confidence, and devise strategies to boost their students’ linguistic competence in the classroom. In order to strengthen students’ capacity for effective oral communication, it is imperative that school officials give more weight to students’ affective development.